PENGARUH TRANSFORMASI SOSIAL PADA PERLINDUNGAN HUKUM PROFESI KEDOKTERAN TERHADAP MALAPRAKTIK MEDIK - Syarifuddin, Andi (Fakultas Hukum, Universitas Muslim Indonesia, 2018)
The influence of social transformation in the relationship between doctor and patient medical in health care, which is unchanged in terms of both the development of science and medical technology as well as in terms of increasingly sophisticated medical equipment. Changes in medicine in adjusting to the development or transformation of science that took place globally, which is more focused on the actualization of resource quality and the perpetrators of medical and actualization of the aspects of the instrument of facilities and infrastructure to support the service in the medical field. In an effort to build a balance or equality impact on the quality of medical services more quality, berkepastian and fair and expediency, legal counseling needs to be done simultaneously to socializing the various aspects of medical law against citizens as the most important stakeholders in the world of medical services. AbstrakPengaruh transformasi sosial dalam hubungan antara dokter dan pasien dalam perawatan kesehatan, yang tidak berubah dalam hal pengembangan ilmu pengetahuan dan teknologi medis serta dalam hal peralatan medis yang semakin canggih. Perubahan ilmu kedokteran dalam menyesuaikan diri dengan perkembangan atau transformasi ilmu yang terjadi secara global, yang lebih fokus pada aktualisasi kualitas sumber daya dan pelaku medis dan aktualisasi aspek instrumen sarana dan prasarana untuk mendukung layanan di bidang medis. Dalam upaya membangun keseimbangan atau dampak kesetaraan pada kualitas layanan medis yang lebih berkualitas, berkepastian dan adil dan bijaksana, konseling hukum perlu dilakukan secara bersamaan untuk mensosialisasikan berbagai aspek hukum kedokteran terhadap warga negara sebagai pemangku kepentingan terpenting di dunia. layanan medis.